Research Progress on the Bacteriostatic Mechanism, Biosynthesis and Application of Phenyllactic Acid - Shuaikang GUO; Na SONG; Guo ZHANG; Pei LI; Ku LI; Xiong CHEN (Shipin gongye ke-ji)
Phenyllactic acid (PLA), produced by many lactic acid bacteria and non-lactic acid bacteria, is a natural substance with broad-spectrum antibacterial properties. As a green product with positive implications for food safety, it has received widespread attention. This work introduces the structure and physicochemical properties of PLA, elaborates on the latest progress in its antibacterial ability, bacteriostatic mechanism, biosynthesis and application. Factors that affect its yield and efficiency in the production process are also illustrated, which provide insights for industrial and market development.